Magnetic-field-induced effects in the electronic structure of itinerant d- and f-metal systems - Grechnev, G.E. (Физика низких температур, 2009)
A paramagnetic response of transition metals and itinerant d- and f -metal compounds in an external magnetic field is studied by employing ab initio full-potential LMTO method in the framework of the local spin density approximation. Within this method the anisotropy of magnetic susceptibility in hexagonal close-packed transition metals is evaluated for the first time. This anisotropy is owing to the orbital Van Vleck-like paramagnetic susceptibility, which is revealed to be substantial in transition metal systems due to hybridization effects in electronic structure. It is demonstrated, that compounds TiCo, Ni₃Al, YCo₂, CeCo₂, YNi₅, LaNi₅ and CeNi₅ are strong paramagnets close to the quantum critical point. For these systems the Stoner approximation underestimates the spin susceptibility, whereas the calculated field-induced spin moments provided a good description of the large paramagnetic susceptibilities and magnetovolume effects. It is revealed, that itinerant description of hybridized f electrons produces magnetic properties of CeCo₂, CeNi₅, UAl₃, UGa₃, USi₃ and UGe₃ compounds in close agreement with experiment. In the uranium UX₃ compounds the strong spin–orbit coupling together with hybridization effects give rise to peculiar magnetic states, where the field-induced spin moments are antiparallel to the external field and the magnetic response is dominated by the orbital contribution.